2016
DOI: 10.2217/rme-2016-0009
|View full text |Cite
|
Sign up to set email alerts
|

Human Limbal Mesenchymal Stem Cells Express ABCB5 and Can Grow on Amniotic Membrane

Abstract: Limbal-derived MSC exhibited plasticity, could maintain limbal markers expression and demonstrated viable growth on amniotic membrane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 56 publications
2
17
0
Order By: Relevance
“…Modeling RPE functional changes, for example basolateral functions, that take place in pathological states like in cases of macular degeneration are more preferable in the form of 3D culture and cell spheroids 15 . The limbal stroma of the eye is one of the promising sources of MSCs 16 . Bioprinting approaches in ophthalmology are used primarily in reconstruction of the anterior segment with the production of artificial cornea and lens that are unique and patient-specific in shape and design 17 .…”
mentioning
confidence: 99%
“…Modeling RPE functional changes, for example basolateral functions, that take place in pathological states like in cases of macular degeneration are more preferable in the form of 3D culture and cell spheroids 15 . The limbal stroma of the eye is one of the promising sources of MSCs 16 . Bioprinting approaches in ophthalmology are used primarily in reconstruction of the anterior segment with the production of artificial cornea and lens that are unique and patient-specific in shape and design 17 .…”
mentioning
confidence: 99%
“…However, our results showed stromal staining of ABCB5 in the limbus, and some LESCs were ABCB5 + /p63α – . A recent study reported that human limbal mesenchymal stem cells also expressed ABCB5 [ 40 ]. In addition, previous studies found that ABCB5 was expressed in skin progenitor cells and melanoma stem cells, and functioned as a regulator of cellular differentiation [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…These data raise questions: whether ABCB5 only marks LESCs in the limbus and whether ABCB5 is a definitive marker of LESCs. Interestingly, two widely proposed LESC markers, p63α and ABCG2, were also expressed in human limbal mesenchymal stem cells [ 40 ], and ABCG2 was also expressed in Langerhans cells rather than LESCs in the limbus [ 43 ]. Thus, we believe that all of these proposed LESC markers are not definitive cell markers only for LESCs.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been suggested that MSCs produce growth factors that can support the growth of residual corneal epithelial cells and LESCs [ 95 ]. Recent researches by Shaharuddin et al found that cultured limbal MSCs expressed the common putative limbal stem cell markers, which demonstrated limbal-derived MSC-exhibited plasticity [ 96 ].…”
Section: Cell-based Therapymentioning
confidence: 99%